Sleep quality in athletes under normobaric hypoxia equivalent to 1500 m altitude: A polysomnographic study - Hoshikawa, M.; Uchida, S.; Sugo, T.; Kumai, Y.; Hanai, Y.; Kawahara, T. (European Journal of Sport Science, 2010)
In the present study, we evaluated the duration of slow-wave sleep (Stage 3 and 4) and total delta power (< 3Hz) in all-night non-rapid eye movement (NREM) sleep electroencephalograms (EEGs) of athletes during normobaric hypoxia at simulated altitudes of 1500 m. Seven male athletes slept for two nights in a normoxic condition and one night in an hypoxic condition equivalent to an altitude of 1500 m. Whole-night polysomnographic recordings, thoracic and abdominal motion, nasal and oral airflow, and blood oxygen saturation (SpO2) were recorded. Visual sleep stage scoring and fast Fourier transformation analyses of EEG were performed using 30-s epochs. Mean and minimum SpO2 decreased significantly during sleep in the hypoxic condition. Between groups, changes in heart rate, respiratory disturbance measures including apnoea and hypopnoea, slow-wave sleep and total delta power of the all-night NREM sleep EEG were small and non-significant for the hypoxic condition. However, individual difference in time at an SpO2 below 90% were large in the hypoxic condition, and both slow-wave sleep and total delta power of all-night NREM sleep EEG decreased in three participants who spent a prolonged time below 90% SpO2. The present results suggest that monitoring time below 90% SpO2 is recommended when studying individuals' living-high schedule even under hypoxic conditions equivalent to an altitude of 1500 m.